Method for manufacturing a catalyst layer for a fuel cell, method for manufacturing a membrane electrode assembly, and method for manufacturing a fuel cell

By using the inclined fibrous conductive member and the catalyst layer of the core-shell catalyst particles in the fuel cell, the problems of gas diffusion and adhesion of the catalyst layer are solved, and the gas diffusion and battery performance of the fuel cell are improved.

JP7627857B2Active Publication Date: 2025-02-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023091134
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-23
Filing Date
2023-06-01
Publication Date
2025-02-07
Estimated Expiration
2038-12-26

AI Technical Summary

Technical Problem

In the existing fuel cells, the gas diffusion properties of the catalyst layer and the aggregation of catalyst particles lead to damage to the electrode film, affecting battery performance, and poor adhesion between the catalyst layer and the gas diffusion layer, affecting reactant supply and moisture discharge.

Method used

A catalyst layer containing fibrous conductive members and catalyst particles is used. The fibrous conductive members are arranged inclined relative to the surface of the catalyst layer, and the length and thickness meet a specific relationship. Catalyst particles with core-shell structure are used to inhibit particle aggregation and improve gas diffusion and adhesion.

Benefits of technology

The gas diffusion and battery performance of the fuel cell are improved, the aggregation of catalyst particles is suppressed, the adhesion between the catalyst layer and the gas diffusion layer is enhanced, and the output characteristics of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627857000002
    Figure 0007627857000002
  • Figure 0007627857000003
    Figure 0007627857000003
  • Figure 0007627857000004
    Figure 0007627857000004
Patent Text Reader

Abstract

To provide a catalyst layer for a fuel cell, with which good gas diffusion properties in the entire catalyst layer can be obtained and in which coarsening of catalyst particles can be suppressed, and also to provide a fuel cell in which the adhesion between a catalyst layer and a gas diffusion layer can be improved, so that the power generation performance of the fuel cell can be enhanced.SOLUTION: A catalyst layer for a fuel cell includes fibrous conductive members and catalyst particles. The fibrous conductive members are inclined relative to a surface direction of the catalyst layer, and the length L of the fibrous conductive members and the thickness T of the catalyst layer satisfy the relational expression: L / T≤3. Each of the catalyst particles includes a core portion and a shell portion that covers the core portion, and contains a component different from that of the core portion.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to a membrane electrode assembly and a fuel cell. [Background technology]

[0002] A fuel cell comprises a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane. Each of the pair of electrodes comprises, in order from the electrolyte membrane side, a catalyst layer and a gas diffusion layer.

[0003] Patent Document 1 proposes using a catalyst layer containing conductive nanocolumns (hereinafter simply referred to as columns) oriented in a direction approximately perpendicular to the surface direction of the catalyst layer (electrolyte membrane) and a catalyst supported on the columns, and interposing an embedding prevention layer between the catalyst layer and the electrolyte membrane.

[0004] The catalyst layer is formed by forming pillars on a substrate by chemical vapor deposition, the pillars being oriented in a direction substantially perpendicular to the surface of the substrate, and then transferring the pillars from the substrate to an electrolyte membrane. The embedding prevention layer is provided to prevent a decrease in catalyst utilization rate due to embedding of the ends of the pillars into the electrolyte membrane during the above-described transfer.

[0005] Patent Document 1 also discloses a gas diffusion layer in which a water-repellent layer containing a conductive material and a water-repellent resin is formed on the catalyst layer side surface of a conductive sheet-like porous substrate (hereinafter simply referred to as substrate), and a gas diffusion layer in which the catalyst layer side of the substrate is impregnated with a water-repellent resin. Patent Document 1 discloses substrates such as carbon paper and carbon cloth, and substrates with a thickness of 50 μm or more.

[0006] On the other hand, Patent Document 2, like Patent Document 1, uses conductive nanocolumns and a catalyst supported on the columns, and proposes that the columns be oriented at an angle of 60° or less with respect to the surface direction of the electrolyte membrane, and that one end of the columns be embedded in the electrolyte membrane. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2013 / 065396 [Patent Document 2] Japanese Patent Application Laid-Open No. 2007-257886 Summary of the Invention

[0008] During the fabrication of a membrane electrode assembly, a single cell, or a stack (cell stack) of multiple single cells, an external force may be applied to the membrane electrode assembly in its thickness direction. The pillars in Patent Document 1 are oriented approximately perpendicular to the surface of the catalyst layer (electrolyte membrane), with both ends of each pillar in contact with the electrolyte membrane and the gas diffusion layer, respectively. Therefore, when an external force is applied in the thickness direction, stress concentrates at both ends of the pillars, potentially causing the pillars to bend or their ends to pierce the electrolyte membrane or the gas diffusion layer. Such a defect results in uneven distribution of voids (gas paths) formed in the catalyst layer, resulting in reduced gas diffusivity in a portion of the catalyst layer. The pillars in Patent Document 2 are oriented obliquely with respect to the surface of the electrolyte membrane, with one end facing the electrolyte membrane embedded in the electrolyte membrane. Similarly, when an external force is applied in the thickness direction of the pillars, the stress applied to the pillars is directly transferred to the electrolyte membrane, resulting in damage to the electrolyte membrane. Furthermore, because the columns are oriented obliquely, stress concentrates on the side surfaces of the columns, causing them to bend. Such bending reduces the distance between adjacent columns, causing deviations in the gas path and resulting in a decrease in gas diffusivity.

[0009] Because the catalyst particles are supported on the smooth surface of the columns, they move along the columnar surface during power generation, causing multiple catalyst particles to aggregate and become coarse. As catalyst particles become coarser, the variation in catalyst particle size increases, which can lead to a decrease in gas diffusivity within the catalyst layer, localized current concentration, and the resulting heat generation that can deteriorate the electrolyte membrane. Furthermore, as catalyst particles become coarser, the coating state of the proton-conductive resin on the catalyst particle surface changes, which can increase proton conduction resistance.

[0010] Furthermore, the gas diffusion layer of Patent Document 1 has low flexibility because it includes the above-mentioned substrate. The gas diffusion layer has difficulty conforming to the surface of the catalyst layer, resulting in low adhesion between the catalyst layer and the gas diffusion layer. The low adhesion between the catalyst layer and the gas diffusion layer affects the supply of reactant gas from the gas diffusion layer to the catalyst layer and the discharge of generated water from the catalyst layer to the gas diffusion layer.

[0011] When a membrane electrode assembly is produced, if high pressure is applied to hot press the catalyst layer and the gas diffusion layer to bond them together, the columns may bend or pierce the gas diffusion layer, as described above, resulting in a decrease in the gas diffusion property of the catalyst layer.

[0012] One aspect of the present disclosure relates to a catalyst layer for a fuel cell comprising a fibrous conductive member and catalyst particles, wherein the length L of the fibrous conductive member and the thickness T of the catalyst layer satisfy the relationship: L / T≦3, and the fibrous conductive member is inclined with respect to the surface direction of the catalyst layer.

[0013] Another aspect of the present disclosure relates to a fuel cell comprising a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane, at least one of the pair of electrodes comprising the above-described catalyst layer.

[0014] Another aspect of the present disclosure relates to a catalyst layer for a fuel cell, comprising a fibrous conductive member and catalyst particles. The fibrous conductive member is inclined with respect to the surface direction of the catalyst layer, and the catalyst particles include first particles each having a core portion and a shell portion. The shell portion covers the core portion and contains a different component from the core portion.

[0015] Another aspect of the present disclosure relates to a fuel cell comprising a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane, at least one of the pair of electrodes comprising the above-described catalyst layer.

[0016] One aspect of the present disclosure relates to a membrane electrode assembly including an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane. Each of the pair of electrodes includes, in order from the electrolyte membrane side, a catalyst layer and a gas diffusion layer. The catalyst layer of at least one of the pair of electrodes includes first fibrous conductive members and catalyst particles. The length L1 of the first fibrous conductive members and the thickness T1 of the catalyst layer satisfy the relationship: L / T≦3, and the first fibrous conductive members are inclined with respect to the surface direction of the catalyst layer. The gas diffusion layer of at least one of the pair of electrodes is composed of a porous layer containing a conductive material and a polymer resin.

[0017] Another aspect of the present disclosure relates to a fuel cell including the above-described membrane electrode assembly and a pair of separators sandwiching the membrane electrode assembly.

[0018] According to the present disclosure, good gas diffusibility can be obtained throughout the catalyst layer, and as a result, the output characteristics of the fuel cell can be improved.

[0019] Furthermore, according to the present disclosure, good gas diffusibility can be obtained throughout the catalyst layer, and coarsening of catalyst particles can be suppressed.

[0020] According to the present disclosure, good gas diffusibility is achieved throughout the catalyst layer, and adhesion between the catalyst layer and the gas diffusion layer is improved, thereby improving the power generation performance of the fuel cell. [Brief explanation of the drawings]

[0021] [Figure 1] 1 is an explanatory diagram illustrating a method for calculating the linearity Lp and the inclination angle θ of a fibrous conductive member using a cross section of a catalyst layer. [Figure 2] 1 is a cross-sectional view schematically showing the structure of a single cell of a fuel cell according to a first embodiment of the present disclosure. [Figure 3] FIG. 2 is a diagram schematically illustrating the inside of a catalyst layer according to the first embodiment of the present disclosure. [Figure 4] FIG. 4 is a cross-sectional view schematically showing a first particle included in the catalyst particle of FIG. [Figure 5]4 is an explanatory diagram illustrating a method for calculating the linearity Lp and the inclination angle θ of a first fibrous conductive member using a cross section of a catalyst layer. FIG. [Figure 6] FIG. 4 is a cross-sectional view schematically showing the structure of a single cell of a fuel cell according to a second embodiment of the present disclosure. [Figure 7] FIG. 4 is a diagram schematically illustrating the inside of a catalyst layer according to a second embodiment of the present disclosure. DETAILED DESCRIPTION OF THE INVENTION

[0022] (First embodiment) A fuel cell catalyst layer according to an embodiment of the present disclosure includes a fibrous conductive member and catalyst particles. The fibrous conductive member is inclined with respect to the surface direction of the catalyst layer (a plane perpendicular to the thickness direction of the catalyst layer). The catalyst particles include first particles (core-shell particles) having a core portion and a shell portion. The shell portion covers the core portion and contains a component different from that of the core portion. A fuel cell according to an embodiment of the present disclosure includes a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane. At least one of the pair of electrodes includes the above-described catalyst layer. That is, the fibrous conductive member is inclined with respect to the surface direction of the electrolyte membrane (a plane perpendicular to the thickness direction of the electrolyte membrane). One of the pair of electrodes is an anode, and the other is a cathode. Hereinafter, the surface direction of the catalyst layer and the surface direction of the electrolyte membrane are also referred to as the XY direction. The thickness direction of the catalyst layer and the thickness direction of the electrolyte membrane are also referred to as the Z direction.

[0023] The fibrous conductive members being inclined with respect to the X and Y directions means that the fibrous conductive members are neither parallel nor perpendicular to the X and Y directions. In other words, the fibrous conductive members are inclined with respect to the X and Y directions and also with respect to the Z direction.

[0024] In this way, by tilting the fibrous conductive members with respect to the XY directions, bending of the fibrous conductive members or piercing of the electrolyte membrane or the like due to the application of external force in the Z direction to the membrane electrode assembly (catalyst layer) is suppressed. Therefore, a decrease in gas diffusibility in a part of the catalyst layer caused by bending of the fibrous conductive members or piercing of the electrolyte membrane or the like is suppressed, and good gas diffusibility is obtained throughout the catalyst layer. Furthermore, the possibility that the conductivity of the fibrous conductive members will be affected by bending of the fibrous conductive members or piercing of the electrolyte membrane or the like is eliminated. Therefore, even without providing an embedding prevention layer, embedding of the ends of the fibrous conductive members into the electrolyte membrane when the catalyst layer is transferred to the electrolyte membrane is suppressed.

[0025] The inclination of the fibrous conductive members means that the fibrous conductive members are present in the catalyst layer at an angle with respect to the X and Y directions while maintaining their linearity. The linearity of the fibrous conductive members is maintained in the catalyst layer when the fibrous conductive members are not significantly bent, and the linearity L obtained by the method described below is p From the viewpoint of further improving gas diffusion, the linearity L p (Average value) is preferably 0.7 or more.

[0026] The direction in which the fibrous conductive members are inclined within the catalyst layer is not particularly limited. The fibrous conductive members included in the catalyst layer may be inclined in different directions or in the same direction.

[0027] The core and shell portions of the first particles contain different components. Incidentally, "the core and shell portions contain different components" means that the metal element with the highest abundance in the core portion is different from the metal element with the highest abundance in the shell portion. When the first particles move along the surface of the fibrous conductive member during power generation, metal agglomeration occurs. However, because agglomeration tends to occur between metals of the same type, the core portions and the shell portions tend to agglomerate separately. This prevents agglomeration that would otherwise result in the entirety of multiple catalyst particles becoming one, thereby preventing the catalyst particles from becoming coarse. Therefore, particle size variation is less likely to increase, localized current concentration and the associated heat generation within the catalyst layer are less likely to occur, and deterioration of the electrolyte membrane is suppressed.

[0028] Typically, the surfaces of catalyst particles are coated with a proton-conductive resin. When the coarsening of catalyst particles is suppressed, the state of the coating of the catalyst particle surfaces with the proton-conductive resin is less likely to change, and an increase in proton conduction resistance is also suppressed.

[0029] When the fibrous conductive member is tilted with respect to the XY direction, the gas diffusibility of the entire catalyst layer is improved, which facilitates the movement of catalyst particles during power generation and is thought to further promote coarsening of the catalyst particles. In contrast, when core-shell particles are used as catalyst particles, the core portions and shell portions aggregate separately, which significantly suppresses the coarsening of catalyst particles even when the gas diffusibility of the entire catalyst layer is significantly improved. In this way, good gas diffusibility is achieved throughout the catalyst layer, and the suppression of catalyst particle coarsening improves the power generation performance (output characteristics, etc.) of the fuel cell. In other words, when the fibrous conductive member is tilted with respect to the XY direction, the suppression of catalyst particle coarsening by the core-shell particles can be particularly pronounced.

[0030] The average particle size of the first particles is preferably, for example, 2 nm to 10 nm, particularly preferably 3 nm to 8 nm. When the average particle size of the first particles is 2 nm or more, sufficient catalytic activity is ensured. When the average particle size of the first particles is 10 nm or less, the electrochemically effective area per gram of the catalyst particles is sufficiently increased. In particular, when the average particle size of the first particles is 3 nm to 8 nm, sufficient catalytic activity is ensured and the sizes of the second and third particles (described below) that may be formed due to the movement of the first particles can be sufficiently reduced.

[0031] The average particle size of the first particles is determined as follows by dismantling an unused fuel cell and taking out the membrane electrode assembly (catalyst layer).

[0032] One first particle is randomly selected from a transmission electron microscope (TEM) image, and its particle diameter is calculated assuming that the particle is spherical. Similarly, the particle diameters of 200 to 300 first particles observed in the same TEM image are calculated. The average value of these particle diameters is taken as the average particle diameter of the first particles. Note that the fact that the catalyst particles present in the catalyst layer are first particles (core-shell particles) is confirmed by composition analysis using energy dispersive X-ray spectroscopy (EDX).

[0033] The components constituting the shell portion may be any as long as they have catalytic activity. From the viewpoint of ensuring high catalytic activity, the shell portion preferably contains at least one of platinum and a platinum alloy. The platinum alloy contains platinum as the main component. The main component here means that the platinum content in the platinum alloy is 90 mass% or more and less than 100 mass%. When the platinum content in the platinum alloy is 90 mass% or more, high catalytic activity and durability are obtained. The platinum alloy contains, for example, at least one element selected from the group consisting of iridium, ruthenium, rhodium, nickel, gold, cobalt, palladium, silver, iron, and copper, in addition to platinum.

[0034] The core portion contains, for example, a transition metal other than platinum. Examples of transition metals other than platinum include palladium, copper, iron, nickel, cobalt, ruthenium, rhodium, silver, and gold. Among transition metals other than platinum, copper, iron, and nickel are preferred from the viewpoint of cost reduction. However, since copper, iron, and nickel are easily eluted from the core portion, it is desirable to select them appropriately depending on the usage environment. The various metals exemplified above may be used alone or in combination of two or more. When two or more types are used in combination, they may be used as an alloy.

[0035] From the viewpoint of suppressing coarsening of catalyst particles and stabilizing the shell portion, the core portion preferably contains at least one of palladium and a palladium alloy. The palladium alloy contains palladium as a main component. "Main component" here means that the palladium content in the palladium alloy is 80% by mass or more and less than 100% by mass. When the palladium content in the palladium alloy is 80% by mass or more, coarsening of catalyst particles is further suppressed. Furthermore, when the palladium content in the palladium alloy is 80% by mass or more, the difference in atomic size between the palladium and the platinum contained in the shell portion becomes small, making it easier to obtain a uniform shell portion. The palladium alloy, for example, contains at least one element selected from the group consisting of iridium, copper, iron, nickel, cobalt, ruthenium, rhodium, and silver in addition to palladium.

[0036] From the viewpoint of ensuring high catalytic activity and suppressing coarsening of catalyst particles, the mass ratio of the shell portion to the first particle is preferably 30 parts by mass or more and 400 parts by mass or less per 100 parts by mass of the core portion, and more preferably 40 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the core portion. In addition, the shell portion preferably has a thickness equivalent to one to four atoms constituting the shell portion.

[0037] Preferably, 70% or more of the surface of the core is covered with the shell, and more preferably, 80% or more of the surface of the core is covered with the shell. When 70% or more of the surface of the core is covered with the shell, high catalytic activity is sufficiently ensured.

[0038] The catalyst particles may further include second particles containing the same components as the core portion. Such second particles can be formed by agglomeration of core portions accompanying the movement of multiple first particles during power generation. The formation of second particles can reduce the size of the aggregated particles compared to when multiple catalyst particles aggregate as a whole. Note that "the second particles and the core portion contain the same components" means that the metal element with the highest abundance ratio in the second particles and the metal element with the highest abundance ratio in the core portion are the same.

[0039] The catalyst particles may further include third particles containing the same components as the shell portion. Such third particles may also be formed by agglomeration of the shell portions associated with the movement of multiple first particles during power generation. The formation of the third particles allows the size of the aggregated particles to be smaller than when multiple catalyst particles aggregate as a whole. Note that "the third particles and the shell portion contain the same components" means that the metal element with the highest abundance ratio in the third particles and the metal element with the highest abundance ratio in the shell portion are the same.

[0040] The second particle and the third particle are derived from the first particle, but can be distinguished from the first particle in that they do not have at least a core-shell structure.

[0041] It is preferable that the length L of the fibrous conductive member and the thickness T of the catalyst layer satisfy the relationship: L / T≦3. When L / T is 3 or less, it is easy to obtain fibrous conductive members that are inclined with respect to the XY direction while maintaining a considerable degree of linearity of the fibrous conductive member. This allows sufficient voids (gas paths) to be formed within the catalyst layer, allowing gas to be effectively diffused throughout the entire catalyst layer.

[0042] From the viewpoint of further improving the gas diffusivity of the catalyst layer, L / T is preferably 0.25 or more and 2.0 or less, and more preferably 0.25 or more and 1.0 or less, which makes it easier to incline the fibrous conductive members within a preferred range of the inclination angle θ described below.

[0043] The length L of the fibrous conductive member is the average fiber length, and is determined by randomly selecting 10 fibrous conductive members from the catalyst layer and averaging the fiber lengths of these fibrous conductive members. Note that the fiber length of the fibrous conductive member refers to the length of a straight line connecting one end of the fibrous conductive member to the other end.

[0044] The length L of the fibrous conductive member is preferably 0.2 μm or more and 20 μm or less, more preferably 0.5 μm or more and 10 μm or less. In this case, even in a thin catalyst layer (e.g., a thickness T of 10 μm or less), the fibrous conductive member can be easily inclined with respect to the surface direction of the catalyst layer. Furthermore, by using a fibrous conductive member having a length within the above range, both ends of the fibrous conductive member are prevented from contacting the electrolyte membrane and the gas diffusion layer, respectively, within the catalyst layer. This further prevents the ends of the fibrous conductive member from being embedded in the electrolyte membrane when the catalyst layer is transferred to the electrolyte membrane, and further prevents the fibrous conductive member from piercing the electrolyte membrane or the like when an external force is applied in the thickness direction of the membrane electrode assembly.

[0045] The thickness T of the catalytic layer is an average thickness, and is obtained by averaging the distances when a straight line is drawn along the thickness direction of the catalytic layer from one main surface to the other main surface at any 10 points on the cross section of the catalytic layer.

[0046] The thickness T of the catalyst layer is preferably thin in consideration of the miniaturization of the fuel cell, but is preferably not excessively thin in terms of strength. The thickness T of the catalyst layer is, for example, 1 μm or more and 50 μm or less, and preferably 2 μm or more and 20 μm or less.

[0047] The inclination angle θ of the fibrous conductive member with respect to the surface direction of the catalyst layer is preferably 80° or less, more preferably 70° or less. When the inclination angle θ is 80° or less, gas diffusibility is further improved in the surface direction of the catalyst layer as well as in the thickness direction of the catalyst layer. When the inclination angle θ is 70° or less, bending of the fibrous conductive member and piercing of the electrolyte membrane or the like due to application of an external force in the thickness direction of the membrane electrode assembly are further suppressed.

[0048] The inclination angle θ of the fibrous conductive members with respect to the surface direction of the catalyst layer is preferably equal to or greater than 25°. When the inclination angle θ is equal to or greater than 25°, gas diffusibility is further improved not only in the surface direction of the catalyst layer but also in the thickness direction of the catalyst layer.

[0049] The inclination angle θ is more preferably 25° or more and 65° or less.

[0050] Linearity L of fibrous conductive material p The linearity L of the fibrous conductive member and the inclination angle θ are calculated as follows, using FIG. p 1 is an explanatory diagram illustrating a method for calculating the axial direction and the inclination angle θ using a cross section of a catalyst layer 120. Only some of the fibrous conductive members 121 are shown in FIG.

[0051] First, a scanning electron microscope (SEM) is used to photograph a cross section along the thickness direction of the catalyst layer 120. The catalyst layer 120 includes fibrous conductive members 121 and catalyst particles (not shown), and has a first main surface 120X on the gas diffusion layer side and a second main surface 120Y on the electrolyte membrane side.

[0052] From the obtained SEM image, a square region (hereinafter referred to as designated region R) is determined, in which, for example, 20 or more fibrous conductive members 121 can be confirmed, and whose one side is the thickness T of the catalyst layer 120. The designated region R can be determined as follows. First, a straight line is drawn along the thickness direction of the catalyst layer 120. The intersection of this line with the second main surface 120Y is set as one of the vertices of the square representing the designated region R. Next, two sides of length T are drawn from this vertex, intersecting perpendicularly to each other, and the remaining two sides are further drawn so as to form a square including the two sides.

[0053] Next, ten identifiable fibrous conductive members 121 are arbitrarily selected from within the designated region R. For each of the ten fibrous conductive members 121, one end of the observable length is connected to the other end with a straight line, and the length L of the line is calculated. s Also, the actual length of the observable part, L r L r L fors Ratio of: L s / L r The linearity factor L p Let's say.

[0054] In the above, the three designated regions R are determined so as not to overlap each other, and the linearity L of the ten fibrous conductive members 121 is set for each of the three designated regions R. p The linearity L of the 30 fibrous conductive members 121 is calculated. p Calculate the average value of the linearity L p When the linearity (average value) is 0.6 or more, it is determined that the linearity of the fibrous conductive member 121 is ensured. p If the average value is less than 0.6, the fibrous conductive members 121 are bent, and the inclination angle θ described below cannot be determined.

[0055] After confirming that the linearity of the fibrous conductive member is ensured by the linearity ratio described above, the inclination angle θ of the fibrous conductive member is determined as follows using FIG.

[0056] A tangent line TL is drawn at the midpoint C of the observable length of each of ten fibrous conductive members 121 selected from each of the three designated regions R. The angle (90° or less) formed by this tangent line TL and the first main surface 120X is defined as the inclination angle θ of the fibrous conductive member 121, and the average value of the inclination angles θ of a total of 30 fibrous conductive members 121 is calculated. If the first main surface 120X has irregularities, the plane perpendicular to the thickness direction of the catalyst layer 120 or the smooth second main surface 120Y may be used as the basis for determining the inclination angle θ.

[0057] The diameter D of the fibrous conductive members is preferably 200 nm or less, more preferably 5 nm or more and 200 nm or less, and even more preferably 8 nm or more and 100 nm or less. In this case, the volume ratio of the fibrous conductive members in the catalyst layer can be reduced, thereby ensuring sufficient gas paths and further improving gas diffusibility.

[0058] The diameter D of the fibrous conductive member is determined by randomly selecting 10 fibrous conductive members from the catalyst layer and averaging their diameters. The diameter is the length perpendicular to the longitudinal direction of the fibrous conductive member.

[0059] It is preferable that the length L of the fibrous conductive member and the diameter D of the fibrous conductive member satisfy the relation: D / L< 1. In this case, good gas diffusibility is sufficiently obtained throughout the catalyst layer.

[0060] From the viewpoint of improving the electrical conductivity, D / L is more preferably 0.002 or more and less than 1.

[0061] From the viewpoint of improving the gas diffusion property of the catalyst layer, the BET specific surface area of ​​the fibrous conductive material is 50 m 2 In this case, the catalyst particles present on the fibrous conductive member are spaced apart at a certain interval or more, thereby ensuring gas diffusibility in the vicinity of the catalyst particles.

[0062] The BET specific surface area of ​​the fibrous conductive member is determined as follows.

[0063] A portion of the prepared catalyst layer is cut out, and the catalyst particles and proton-conductive resin are removed from the cut-out sample to extract the fibrous conductive member. The specific surface area of ​​the fibrous conductive member is determined by the BET method, a common method for measuring specific surface area, using a specific surface area measurement device based on the gas adsorption method.

[0064] Examples of the fibrous conductive members 121 include carbon fibers such as vapor grown carbon fibers (VGCF), carbon nanotubes (CNT), and carbon nanofibers.

[0065] At least a portion of the catalyst particles are supported on the fibrous conductive member. It is preferable that the catalyst particles are supported on the particulate conductive member described below in addition to the fibrous conductive member. This is because the catalyst particles are more likely to come into contact with the gas, thereby increasing the efficiency of the gas oxidation or reduction reaction.

[0066] The catalyst particles are not particularly limited, but examples thereof include catalyst metals such as alloys or simple substances selected from Sc, Y, Ti, Zr, V, Nb, Fe, Co, Ni, Ru, Rh, Pd, Pt, Os, Ir, lanthanide series elements, and actinide series elements. For example, catalyst particles used in the anode include Pt and Pt-Ru alloys. For example, catalyst metals used in the cathode include Pt and Pt-Co alloys.

[0067] From the viewpoint of shortening the conductive path and further increasing the conductivity, it is preferable that the catalyst layer further contains a particulate conductive material. The particulate conductive material is not particularly limited, but carbon black is preferred because of its excellent conductivity. Examples of carbon black include acetylene black, ketjen black, thermal black, furnace black, and channel black. There are no particular limitations on the particle size (or the length of the structure composed of multiple connected primary particles), and those conventionally used in catalyst layers for fuel cells can be used.

[0068] The content of the particulate conductive material in the catalyst layer is preferably 40 parts by mass or less, more preferably 5 parts by mass or more and 35 parts by mass or less, and even more preferably 10 parts by mass or more and 30 parts by mass or less, per 100 parts by mass of the total of the fibrous conductive material and the particulate conductive material. In this case, the conductivity can be increased while maintaining good gas diffusibility throughout the catalyst layer.

[0069] From the viewpoint of improving the reactivity of the catalyst layer, it is preferable that the catalyst layer further contains a proton-conductive resin. In this case, the proton-conductive resin coats at least a portion of the fibrous conductive members and the catalyst particles. Because the fibrous conductive members are inclined with respect to the surface direction of the catalyst layer, the effect on the reactivity (proton conductivity) of the catalyst layer caused by bending of the fibrous conductive members due to application of an external force in the thickness direction of the membrane electrode assembly is suppressed.

[0070] The proton conductive resin is not particularly limited, but examples thereof include perfluorocarbon sulfonic acid polymers, hydrocarbon polymers, etc. Among them, perfluorocarbon sulfonic acid polymers, etc. are preferred because of their excellent heat resistance and chemical stability. An example of a perfluorocarbon sulfonic acid polymer is Nafion (registered trademark). The proton conductive resin may further coat at least a portion of the particulate conductive member.

[0071] The content of the fibrous conductive member in the catalyst layer is preferably 15 to 65 parts by mass, more preferably 20 to 55 parts by mass, relative to 100 parts by mass of the total of the catalyst particles, particulate carbon material, and proton conductive resin, because this makes it easier for the fibrous conductive member to be arranged in a desired state, which tends to improve gas diffusion properties and the efficiency of the electrochemical reaction.

[0072] The catalyst layer can be formed, for example, by applying a catalyst ink containing fibrous conductive members and catalyst particles to the surface of the electrolyte membrane and drying it. Alternatively, the catalyst ink can be applied to a transfer substrate sheet, dried to form a catalyst layer, and the catalyst layer formed on the substrate sheet can be transferred to the electrolyte membrane. Because the fibrous conductive members are inclined relative to the surface direction of the catalyst layer, embedding of the fibrous conductive members into the electrolyte membrane during transfer of the catalyst layer is suppressed even without an embedding prevention layer being placed on the surface of the electrolyte membrane. As the substrate sheet, it is preferable to use a sheet with a smooth surface, such as polyethylene terephthalate (PET) or polypropylene.

[0073] In addition to the fibrous conductive members and catalyst particles, the catalyst ink also contains a dispersion medium, such as water, ethanol, or propanol. The catalyst ink may further contain particulate conductive members, a proton-conductive resin, and the like.

[0074] Examples of application methods include spraying, screen printing, and coating methods using various coaters such as a blade coater, a knife coater, a gravure coater, etc. When a coater is used, it is easy to control the tilt direction of the fibrous conductive members.

[0075] Fibrous conductive members that are inclined relative to the surface direction of the catalyst layer (electrolyte membrane) can be obtained by adjusting the length of the fibrous conductive members and the thickness of the catalyst layer so that the L / T ratio is 3 or less when forming the catalyst layer by applying catalyst ink. The length of the fibrous conductive members can be adjusted by appropriately selecting the length of the material used for the fibrous conductive members. The thickness of the catalyst layer can be adjusted by changing the amount of catalyst ink applied, etc.

[0076] The inclination angle θ of the fibrous conductive members can be adjusted by, for example, changing the composition, viscosity, application amount, application speed, drying speed, etc. of the catalyst ink.

[0077] A polymer electrolyte membrane is preferably used as the electrolyte membrane. Materials for the polymer electrolyte membrane include the polymer electrolytes exemplified as the proton-conductive resin. The thickness of the electrolyte membrane is, for example, 5 to 30 μm.

[0078] The gas diffusion layer may have a structure with or without a substrate layer. An example of a structure with a substrate layer is a structure with a substrate layer and a microporous layer provided on the catalyst layer side. A conductive porous sheet such as carbon cloth or carbon paper is used for the substrate layer. A mixture of a water-repellent resin such as a fluororesin, a conductive carbon material, and a proton-conductive resin (polymer electrolyte) is used for the microporous layer.

[0079] An example of the structure of a fuel cell according to this embodiment will be described below with reference to FIG. 2. FIG. 2 is a cross-sectional view that schematically shows the structure of a unit cell that is arranged in a fuel cell according to this embodiment of the present invention. Typically, a plurality of unit cells are stacked and arranged in the fuel cell as a cell stack. For convenience, FIG. 2 shows one unit cell.

[0080] Each unit cell of the fuel cell 200 includes an electrolyte membrane 110 and a first catalyst layer 120A and a second catalyst layer 120B arranged to sandwich the electrolyte membrane 110. Each unit cell of the fuel cell 200 further includes a first gas diffusion layer 130A and a second gas diffusion layer 130B arranged to sandwich the electrolyte membrane 110 with the first catalyst layer 120A and the second catalyst layer 120B interposed therebetween, and a first separator 240A and a second separator 240B arranged to sandwich the electrolyte membrane 110 with the first gas diffusion layer 130A and the second gas diffusion layer 130B interposed therebetween. One of the first catalyst layer 120A and the second catalyst layer 120B functions as an anode, and the other functions as a cathode. Because the electrolyte membrane 110 is slightly larger than the first catalyst layer 120A and the second catalyst layer 120B, the peripheral edge of the electrolyte membrane 110 protrudes from the first catalyst layer 120A and the second catalyst layer 120B. The peripheral edge of the electrolyte membrane 110 is sandwiched between a pair of sealing members 250A and 250B.

[0081] At least one of the first catalyst layer 120A and the second catalyst layer 120B is the catalyst layer 120 shown in FIG. 3. FIG. 3 is a diagram schematically illustrating the interior of the catalyst layer, viewed from the surface. For convenience, the electrolyte membrane 110 is also shown to illustrate the inclination of the fibrous conductive members. As shown in FIG. 3, the catalyst layer 120 includes fibrous conductive members 121 and catalyst particles 122. The fibrous conductive members 121 are inclined with respect to the surface of the electrolyte membrane 110, and the length L of the fibrous conductive members 121 and the thickness T of the catalyst layer 120 satisfy the relationship: L / T≦3. When the first catalyst layer 120A or the second catalyst layer 120B is not the above-described catalyst layer 120, known materials and known configurations can be used for the catalyst layer.

[0082] At least one of the first gas diffusion layer 130A and the second gas diffusion layer 130B is the above-mentioned gas diffusion layer. Either the first gas diffusion layer 130A or the second gas diffusion layer 130B may have the same configuration as the above-mentioned gas diffusion layer.

[0083] The first separator 240A and the second separator 240B may be made of any material, as long as they are airtight, electronically conductive, and electrochemically stable. Carbon materials, metal materials, and the like are preferred. Metal materials may be coated with carbon. For example, the first separator 240A and the second separator 240B can be obtained by punching a metal plate into a predetermined shape and then subjecting it to a surface treatment.

[0084] In this embodiment, a gas flow channel 260A is formed on the surface of the first separator 240A that comes into contact with the first gas diffusion layer 130A. Meanwhile, a gas flow channel 260B is formed on the surface of the second separator 240B that comes into contact with the second gas diffusion layer 130B. The shape of the gas flow channel is not particularly limited, and may be a parallel type, a serpentine type, or the like.

[0085] Seal members 250A, 250B are made of an elastic material and prevent leakage of fuel and / or oxidant from gas flow paths 260A, 260B. Seal members 250A, 250B have, for example, a frame-like shape that surrounds the peripheral edges of first catalyst layer 120A and second catalyst layer 120B in a loop shape. Seal members 250A, 250B can each be made of a known material and have a known configuration.

[0086] The catalyst particle 122 includes a first particle 122A shown in FIG. 4. FIG. 4 is a cross-sectional view schematically showing the first particle 122A. The first particle 122A includes a core portion 122B and a shell portion 122C that covers the core portion 122B and contains a component different from that of the core portion 122B. The catalyst particle 122 may further include the second particle and third particle described above. When the first catalyst layer 120A or the second catalyst layer 120B is not the above-described catalyst layer 120, a known material and a known configuration can be used as the catalyst layer.

[0087] At least one of the first gas diffusion layer 130A and the second gas diffusion layer 130B is the above-mentioned gas diffusion layer. Either the first gas diffusion layer 130A or the second gas diffusion layer 130B may have the same configuration as the above-mentioned gas diffusion layer.

[0088] The first separator 240A and the second separator 240B may be made of any material, as long as they are airtight, electronically conductive, and electrochemically stable. Carbon materials, metal materials, and the like are preferred. Metal materials may be coated with carbon. For example, the first separator 240A and the second separator 240B can be obtained by punching a metal plate into a predetermined shape and then subjecting it to a surface treatment.

[0089] In this embodiment, a gas flow channel 260A is formed on the surface of the first separator 240A that comes into contact with the first gas diffusion layer 130A. Meanwhile, a gas flow channel 260B is formed on the surface of the second separator 240B that comes into contact with the second gas diffusion layer 130B. The shape of the gas flow channel is not particularly limited, and may be a parallel type, a serpentine type, a straight type, or the like.

[0090] Seal members 250A, 250B are made of an elastic material and prevent leakage of fuel and / or oxidant from gas flow paths 260A, 260B. Seal members 250A, 250B have, for example, a frame-like shape that surrounds the peripheral edges of first catalyst layer 120A and second catalyst layer 120B in a loop shape. Seal members 250A, 250B can each be made of a known material and have a known configuration.

[0091] The present invention will be described in more detail below based on examples, although the present invention is not limited to the following examples.

[0092] [Example 1] <Fabrication of membrane electrode assembly> A fibrous conductive member carrying catalyst particles (Pt) was added to an appropriate amount of water and then stirred to disperse. CNTs (average diameter 15 nm, average fiber length 15 μm) were used as the fibrous conductive member. In this case, the catalyst particles were 50 parts by mass and the fibrous conductive member were 50 parts by mass, with a total of 100 parts by mass of the catalyst particles and fibrous conductive member. Next, an appropriate amount of ethanol was added to the resulting dispersion while stirring, and then 30 parts by mass of a proton-conductive resin (Nafion (registered trademark)) was added to 50 parts by mass of the fibrous conductive member. This was stirred to prepare a catalyst ink for a cathode catalyst layer.

[0093] Particulate conductive material (acetylene black) carrying catalyst particles (Pt) was added to an appropriate amount of water, and then stirred to disperse. At this time, the catalyst particles were 50 parts by mass and the particulate conductive material were 50 parts by mass, with a total of 100 parts by mass of the catalyst particles and the particulate conductive material. Next, an appropriate amount of ethanol was added to the resulting dispersion while stirring, and then 40 parts by mass of a proton-conductive resin (Nafion (registered trademark)) was added to 50 parts by mass of the particulate conductive material. This was stirred to prepare a catalyst ink for the anode catalyst layer.

[0094] A Nafion (registered trademark) membrane (thickness: 15 μm) was prepared as the electrolyte membrane. A catalyst ink for a cathode catalyst layer was applied to the cathode-side main surface of the electrolyte membrane by spraying, and then left to dry in an atmosphere at 70°C for 3 minutes to form a cathode catalyst layer. The amount of catalyst ink applied for the cathode catalyst layer was adjusted so that the thickness of the cathode catalyst layer was 6 μm. Next, a catalyst ink for an anode catalyst layer was applied to the anode-side main surface of the electrolyte membrane by spraying, and then left to dry in an atmosphere at 70°C for 3 minutes to form an anode catalyst layer.

[0095] Two conductive porous sheets with a microporous layer (MPL) on one main surface were prepared as gas diffusion layers. A gas diffusion layer was placed on the main surface of the anode catalyst layer opposite the electrolyte membrane, with the microporous layer facing the anode catalyst layer. A gas diffusion layer was placed on the main surface of the cathode catalyst layer opposite the electrolyte membrane, with the microporous layer facing the cathode catalyst layer. The electrolyte membrane and the pair of catalyst layers sandwiching the electrolyte membrane and the gas diffusion layer were then integrated by heat pressing to produce a membrane electrode assembly. A frame-shaped sealing member was placed to surround the anode and cathode.

[0096] The cross section of the obtained membrane electrode assembly was photographed using an SEM. The SEM image confirmed that a portion of the catalyst particles was supported on the fibrous conductive member. Using this SEM image, the thickness T of the cathode catalyst layer was determined to be 6 μm using the method described above. The length L of the fibrous conductive member was determined to be 15 μm, and the diameter D of the fibrous conductive member was determined to be 15 nm using the method described above. From the length L of the fibrous conductive member and the thickness T of the cathode catalyst layer determined above, the L / T ratio was calculated to be 15 / 6.

[0097] The linearity Lp determined by the previously described method was 0.6 or greater, confirming that the linearity of the fibrous conductive member was maintained. The inclination angle θ of the fibrous conductive member relative to the surface direction of the cathode catalyst layer determined by the previously described method was 30°, confirming that the fibrous conductive member was not lying down. SEM images also confirmed that the fibrous conductive member did not pierce the electrolyte membrane or gas diffusion layer.

[0098] <Production of a single cell> The membrane electrode assembly was sandwiched between a pair of stainless steel flat plates (separators) to complete the test unit cell A1. Gas flow channels were formed on the surface of the separator that came into contact with the gas diffusion layer.

[0099] <Evaluation> Using the single cell A1 of Example 1, the IV characteristics were measured under the conditions of a cell temperature of 80°C, a gas utilization rate of 50%, and a relative humidity of 100%, and the maximum power density was measured. The maximum power density is expressed as an index, with the maximum power density of the single cell B1 of Comparative Example 1 set to 100.

[0100] [Example 2] A single cell A2 was fabricated and evaluated in the same manner as in Example 1, except that CNTs with an average fiber length of 5 μm were used for the fibrous conductive member. The length L of the fibrous conductive member determined by the method described above was 5 μm, and the thickness T of the cathode catalyst layer was 6 μm. From this, L / T was calculated to be 5 / 6.

[0101] The linearity Lp determined by the previously described method was 0.6 or greater, confirming that the linearity of the fibrous conductive member was maintained. The inclination angle θ of the fibrous conductive member relative to the surface direction of the cathode catalyst layer determined by the previously described method was 45°, confirming that the fibrous conductive member was not lying down. SEM images also confirmed that the fibrous conductive member did not pierce the electrolyte membrane or gas diffusion layer.

[0102] [Example 3] Similarly, a single cell A3 was fabricated and evaluated in the same manner as in Example 1, except that CNTs with an average fiber length of 15 μm were used for the fibrous conductive member. The length L of the fibrous conductive member determined by the method described above was 100 μm, and the thickness T of the catalyst layer was 5 μm. From this, the L / T ratio was calculated to be 15 / 5 (L / T=3).

[0103] The linearity Lp determined by the previously described method was 0.6 or greater, confirming that the linearity of the fibrous conductive member was maintained. The inclination angle θ of the fibrous conductive member relative to the surface direction of the cathode catalyst layer determined by the previously described method was 28°, confirming that the fibrous conductive member was not lying down. SEM images also confirmed that the fibrous conductive member did not pierce the electrolyte membrane or gas diffusion layer.

[0104] [Comparative Example 1] A single cell B1 was produced and evaluated in the same manner as in Example 1, except that CNTs with an average fiber length of 100 μm were used for the fibrous conductive member. The length L of the fibrous conductive member determined by the method described above was 100 μm, and the thickness T of the catalyst layer was 6 μm. From this, L / T was calculated to be 100 / 6.

[0105] The linearity L obtained by the above method p The inclination angle θ could not be determined because the angle was less than 0.6, and bending of the fibrous conductive members was confirmed. SEM images also confirmed that the fibrous conductive members were lying down. The bending and lying down of the fibrous conductive members are thought to be due to the length L of the fibrous conductive members being excessively large compared to the thickness T of the catalyst layer. This confirmed the reduction and uneven distribution of voids within the cathode catalyst layer.

[0106] The evaluation results are shown in Table 1.

[0107] [Table 1]

[0108] In the single cells A1 to A3 of Examples 1 to 3, the gas diffusibility of the catalyst layer was improved, and therefore a high maximum power density was obtained, compared to the single cell B1 of Comparative Example 1. A2 of Example 2, in which L / T was 1 or less, exhibited even higher power output characteristics than A1 of Example 1, in which L / T was greater than 1 and 3 or less.

[0109] (Second embodiment) A membrane electrode assembly according to a second embodiment of the present disclosure includes an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane. Each of the pair of electrodes includes, in order from the electrolyte membrane side, a catalyst layer and a gas diffusion layer. The catalyst layer of at least one of the pair of electrodes includes first fibrous conductive members and catalyst particles, and the first fibrous conductive members are inclined with respect to the surface direction of the catalyst layer (the surface direction of the electrolyte membrane). The gas diffusion layer of at least one of the pair of electrodes is composed of a porous layer containing a conductive material and a polymer resin. One of the pair of electrodes is an anode, and the other is a cathode. A fuel cell according to an embodiment of the present invention includes a membrane electrode assembly and a pair of separators sandwiching the membrane electrode assembly. Hereinafter, the surface direction of the catalyst layer and the surface direction of the electrolyte membrane will also be referred to as the XY direction. The thickness direction of the catalyst layer and the thickness direction of the electrolyte membrane will also be referred to as the Z direction.

[0110] The first fibrous conductive members being inclined with respect to the XY directions means that the first fibrous conductive members are neither parallel nor perpendicular to the XY directions. In other words, the first fibrous conductive members are inclined with respect to the XY directions and also with respect to the Z direction.

[0111] By tilting the first fibrous conductive members with respect to the XY direction, bending of the first fibrous conductive members or piercing of the electrolyte membrane or the like due to application of external force in the Z direction to the membrane electrode assembly (catalyst layer) is suppressed. Therefore, a decrease in gas diffusibility in a portion of the catalyst layer caused by bending of the first fibrous conductive members or piercing of the electrolyte membrane or the like is suppressed, and good gas diffusibility is obtained throughout the catalyst layer. Furthermore, the possibility that bending of the first fibrous conductive members or piercing of the electrolyte membrane or the like will affect the conductivity of the first fibrous conductive members is eliminated. Even without providing an embedding prevention layer, embedding of the ends of the first fibrous conductive members into the electrolyte membrane when the catalyst layer is transferred to the electrolyte membrane is suppressed.

[0112] The inclination of the first fibrous conductive members means that the first fibrous conductive members are present in the catalyst layer at an angle with respect to the X and Y directions while maintaining their linearity. The linearity of the first fibrous conductive members is maintained in the catalyst layer when the first fibrous conductive members are not significantly bent, and the linearity L calculated by the method described below is p From the viewpoint of further improving gas diffusion, the linearity L p (Average value) is preferably 0.7 or more.

[0113] The direction in which the first fibrous conductive members are inclined within the catalyst layer is not particularly limited, and the first fibrous conductive members included in the catalyst layer may be inclined in different directions or in the same direction.

[0114] The gas diffusion layer is made of the porous layer and therefore has good flexibility. Therefore, by using the catalyst layer and the gas diffusion layer in combination, the gas diffusion layer can adequately conform to the surface of the catalyst layer when the gas diffusion layer is placed on the catalyst layer, significantly improving adhesion between the catalyst layer and the gas diffusion layer. This allows for smooth supply of reactant gas from the gas diffusion layer to the catalyst layer and smooth discharge of generated water from the catalyst layer to the gas diffusion layer. The generated water includes water generated by at least one of catalytic reaction and condensation within the catalyst layer.

[0115] A membrane electrode assembly can be obtained, for example, by sandwiching an electrolyte membrane, which has catalyst layers formed on both sides, between a pair of gas diffusion layers to form a laminate, and then hot-pressing the laminate. By using a catalyst layer including first fibrous conductive members that are inclined with respect to the surface direction of the catalyst layer in combination with a flexible gas diffusion layer, the catalyst layer and the gas diffusion layer can be sufficiently adhered to each other by hot-pressing at low pressure. This prevents the first fibrous conductive members from bending or piercing the gas diffusion layer during fabrication of the membrane electrode assembly, thereby improving the gas diffusion properties of the catalyst layer.

[0116] When the first fibrous conductive members are inclined relative to the surface direction of the catalyst layer, there may be some disadvantages in terms of drainage from the catalyst layer to the gas diffusion layer, depending on the degree of inclination of the first fibrous conductive members and the longitudinal direction of the first fibrous conductive members when viewed from the stacking direction of the membrane electrode assembly. Even in such cases, the significantly improved adhesion between the catalyst layer and the gas diffusion layer sufficiently improves drainage from the catalyst layer to the gas diffusion layer.

[0117] Good gas diffusion properties are obtained throughout the catalyst layer, and the adhesion between the catalyst layer and the gas diffusion layer is improved, thereby improving the power generation performance (output characteristics, etc.) of the fuel cell.

[0118] (catalyst layer) It is preferable that the length L1 of the first fibrous conductive members and the thickness T1 of the catalyst layer satisfy the relationship: L1 / T1≦3. When L1 / T1 is 3 or less, it is easy to obtain first fibrous conductive members that are inclined with respect to the XY direction while maintaining a considerable degree of linearity of the first fibrous conductive members. This allows sufficient voids (gas paths) to be formed within the catalyst layer, allowing gas to diffuse effectively throughout the entire catalyst layer.

[0119] From the viewpoint of further improving the gas diffusivity of the catalyst layer, L1 / T1 is preferably 0.25 or more and 2.0 or less, and more preferably 0.25 or more and 1.0 or less, which makes it easier to incline the first fibrous conductive members within a preferred range of the inclination angle θ described below.

[0120] The length L1 of the first fibrous conductive members is the average fiber length, and is determined by randomly selecting 10 first fibrous conductive members from the catalyst layer and averaging the fiber lengths of these first fibrous conductive members. Note that the fiber length of the first fibrous conductive members refers to the length of a straight line connecting one end of the first fibrous conductive members to the other end.

[0121] The length L1 of the first fibrous conductive member is preferably 0.2 μm or more and 20 μm or less, more preferably 0.5 μm or more and 10 μm or less. In this case, even in a thin catalyst layer (e.g., a thickness T1 of 10 μm or less), the first fibrous conductive member can be easily tilted with respect to the XY direction. Furthermore, using first fibrous conductive members short in the above ranges prevents both ends of the first fibrous conductive member from contacting the electrolyte membrane and gas diffusion layer, respectively, within the catalyst layer. This further prevents the ends of the first fibrous conductive member from being embedded in the electrolyte membrane when the catalyst layer is transferred to the electrolyte membrane. Furthermore, this further prevents the first fibrous conductive member from piercing the electrolyte membrane or the like when an external force in the Z direction is applied to the membrane electrode assembly.

[0122] The thickness T1 of the catalytic layer is an average thickness, and is determined by averaging the distances when a straight line is drawn along the thickness direction of the catalytic layer from one main surface to the other main surface at any 10 points on the cross section of the catalytic layer.

[0123] The thickness T1 of the catalyst layer is preferably thin in consideration of miniaturization of the fuel cell, but is not excessively thin in terms of strength. The thickness T of the catalyst layer is, for example, 1 μm or more and 50 μm or less, and preferably 2 μm or more and 20 μm or less.

[0124] The inclination angle θ of the first fibrous conductive member with respect to the X and Y directions is preferably 80° or less, and more preferably 70° or less. When the inclination angle θ is 80° or less, gas diffusibility is further improved in the X and Y directions as well as in the Z direction. When the inclination angle θ is 70° or less, bending of the first fibrous conductive member and piercing of the electrolyte membrane or the like due to application of an external force in the Z direction to the membrane electrode assembly are further suppressed.

[0125] The inclination angle θ of the first fibrous conductive members with respect to the XY directions is preferably equal to or greater than 25°. When the inclination angle θ is equal to or greater than 25°, gas diffusibility is further improved in the Z direction in addition to the XY directions.

[0126] The inclination angle θ is more preferably 25° or more and 65° or less.

[0127] Linearity L of the first fibrous conductive member p The linearity L of the first fibrous conductive member and the inclination angle θ can be calculated as follows using FIG. p 5 is an explanatory diagram illustrating a method for calculating the inclination angle θ using a cross section of a catalyst layer 120. Fig. 5 shows only a portion of first fibrous conductive members 121A.

[0128] First, a scanning electron microscope (SEM) is used to photograph a cross section along the thickness direction of the catalyst layer 120. The catalyst layer 120 includes first fibrous conductive members 121A and catalyst particles (not shown), and has a first main surface 120X on the gas diffusion layer side and a second main surface 120Y on the electrolyte membrane side.

[0129] From the obtained SEM image, a square region (hereinafter referred to as designated region R) is determined, in which, for example, 20 or more first fibrous conductive members 121A can be confirmed, and whose one side is the thickness T of the catalyst layer 120. The designated region R can be determined as follows. First, a straight line is drawn along the thickness direction of the catalyst layer 120. The intersection of this line with the second main surface 120Y is set as one of the vertices of the square representing the designated region R. Next, two sides of length T are drawn from this vertex, intersecting perpendicularly to each other, and the remaining two sides are then drawn so as to form a square including the two sides.

[0130] Next, ten first fibrous conductive members 121A that can be observed within the designated region R are arbitrarily selected. For each of the ten first fibrous conductive members 121A, one end and the other end of the observable length are connected by a straight line, and the length L of the line is calculated. s Also, the actual length of the observable part, L r L r L for s Ratio of: L s / L r The linearity factor L p Let's say.

[0131] In the above, the three designated regions R are determined so as not to overlap each other, and the linearity L of the ten first fibrous conductive members 121A is set for each of the three designated regions R. p The linearity L of the total 30 first fibrous conductive members 121A was calculated. p Calculate the average value of the linearity L p When the linearity ratio L (average value) is 0.6 or more, it is determined that the linearity of the first fibrous conductive member 121A is ensured. p If the average value is less than 0.6, it is determined that the first fibrous conductive member 121A is bent, and the inclination angle θ, which will be described later, cannot be determined.

[0132] After confirming that the linearity of the first fibrous conductive member is ensured by the above linearity ratio, the inclination angle θ of the first fibrous conductive member can be determined using the diagram as follows.

[0133] A tangent line TL is drawn at the midpoint C of the observable length of each of ten first fibrous conductive members 121A selected from each of the three designated regions R. The angle (90° or less) formed by this tangent line TL and first main surface 120X is defined as the inclination angle θ of that first fibrous conductive member 121A, and the average value of the inclination angles θ of a total of 30 first fibrous conductive members 121A is calculated. If first main surface 120X has irregularities, the surface perpendicular to the thickness direction of catalyst layer 120 or smooth second main surface 120Y may be used as the basis for determining the inclination angle θ.

[0134] The diameter D1 of the first fibrous conductive members is preferably 200 nm or less, more preferably 5 nm or more and 200 nm or less, and even more preferably 8 nm or more and 100 nm or less. In this case, the volume ratio of the first fibrous conductive members in the catalyst layer can be reduced, thereby ensuring sufficient gas paths and further improving gas diffusibility.

[0135] The diameter D1 of the first fibrous conductive members is determined by randomly selecting 10 first fibrous conductive members from the catalyst layer and averaging their diameters. The diameter is the length perpendicular to the length of the first fibrous conductive members.

[0136] It is preferable that the length L1 of the first fibrous electrically conductive members and the diameter D1 of the first fibrous electrically conductive members satisfy the relationship: D1 / L1<1. In this case, sufficient good gas diffusibility is obtained throughout the catalyst layer.

[0137] From the viewpoint of improving the electrical conductivity, D1 / L1 is more preferably 0.002 or more and less than 1.

[0138] From the viewpoint of improving the gas diffusion property of the catalyst layer, the BET specific surface area of ​​the first fibrous conductive member is 50 m 2 In this case, a certain amount of spacing between catalyst particles present on the first fibrous electrically conductive member is ensured, thereby ensuring gas diffusibility in the vicinity of the catalyst particles.

[0139] The BET specific surface area of ​​the first fibrous conductive members is determined as follows.

[0140] A portion of the prepared catalyst layer is cut out, and the catalyst particles and proton-conductive resin are removed from the cut-out sample to extract a first fibrous conductive member. The specific surface area of ​​the first fibrous conductive member is determined by the BET method, a common method for measuring specific surface area, using a specific surface area measurement device based on the gas adsorption method.

[0141] Examples of the first fibrous conductive members include carbon fibers such as vapor grown carbon fibers (VGCF), carbon nanotubes (CNT), and carbon nanofibers.

[0142] At least a portion of the catalyst particles are supported on the first fibrous conductive members. Preferably, the catalyst particles are supported on the particulate conductive members described below in addition to the first fibrous conductive members. This facilitates contact of the catalyst particles with gas, thereby increasing the efficiency of the gas oxidation or reduction reaction.

[0143] The catalyst particles are not particularly limited, but examples thereof include catalyst metals such as alloys or simple substances selected from Sc, Y, Ti, Zr, V, Nb, Fe, Co, Ni, Ru, Rh, Pd, Pt, Os, Ir, lanthanide series elements, and actinide series elements. For example, catalyst particles used in the anode include Pt and Pt-Ru alloys. For example, catalyst metals used in the cathode include Pt and Pt-Co alloys.

[0144] From the viewpoint of shortening the conductive path and further increasing the conductivity, it is preferable that the catalyst layer further contains a particulate conductive material. The particulate conductive material is not particularly limited, but carbon black is preferred because of its excellent conductivity. Examples of carbon black include acetylene black, ketjen black, thermal black, furnace black, and channel black. There are no particular limitations on the particle size (or the length of the structure composed of multiple connected primary particles), and any material conventionally used in catalyst layers for fuel cells can be used.

[0145] The content of the particulate conductive members in the catalyst layer is preferably 40 parts by mass or less, more preferably 5 parts by mass or more and 35 parts by mass or less, and even more preferably 10 parts by mass or more and 30 parts by mass or less, per 100 parts by mass of the total of the first fibrous conductive members and the particulate conductive members. In this case, the conductivity can be increased while maintaining good gas diffusibility throughout the catalyst layer.

[0146] From the viewpoint of improving the reactivity of the catalyst layer, it is preferable that the catalyst layer further contains a proton-conductive resin. In this case, the proton-conductive resin coats at least a portion of the first fibrous conductive members and the catalyst particles. Because the first fibrous conductive members are inclined with respect to the XY direction, the effect on the reactivity (proton conductivity) of the catalyst layer caused by bending of the first fibrous conductive members due to application of an external force in the Z direction to the membrane electrode assembly is suppressed.

[0147] The proton conductive resin is not particularly limited, but examples thereof include perfluorocarbon sulfonic acid polymers, hydrocarbon polymers, etc. Among them, perfluorocarbon sulfonic acid polymers, etc. are preferred because of their excellent heat resistance and chemical stability. An example of a perfluorocarbon sulfonic acid polymer is Nafion (registered trademark). The proton conductive resin may further coat at least a portion of the particulate conductive member.

[0148] The content of the first fibrous conductive members in the catalyst layer is preferably 15 to 65 parts by mass, more preferably 20 to 55 parts by mass, relative to 100 parts by mass of the total of the catalyst particles, particulate carbon material, and proton-conductive resin, because this makes it easier for the first fibrous conductive members to be arranged in a desired state, which tends to improve gas diffusion and electrochemical reaction efficiency.

[0149] The porosity P1 of the catalyst layer is preferably 30% or more and 70% or less, more preferably 40% or more and 65% or less, which tends to improve both gas diffusion and drainage in the catalyst layer.

[0150] The porosity P1 of the catalyst layer is determined as follows.

[0151] An image of the cross section of the catalyst layer is taken using a scanning electron microscope (SEM). The obtained image is subjected to image processing (binarization processing) so that the void portion can be distinguished from the non-void portion. An area of ​​a predetermined area A1 is arbitrarily selected from the processed image, and the area A of the voids present in that area is calculated. p1 Calculate the area of ​​the void A relative to the area A1 of the region. p1 The ratio (%) of the above is calculated and set as the porosity P1. A plurality of porosities may be calculated for a plurality of regions, and these may be averaged.

[0152] (Formation of catalyst layer) The catalyst layer can be formed, for example, by applying a catalyst ink containing first fibrous conductive members and catalyst particles to the surface of the electrolyte membrane and drying it. Alternatively, the catalyst ink may be applied to a transfer substrate sheet, dried to form a catalyst layer, and the catalyst layer formed on the substrate sheet may be transferred to the electrolyte membrane. As the substrate sheet, it is preferable to use a sheet with a smooth surface, such as polyethylene terephthalate (PET) or polypropylene.

[0153] In addition to the first fibrous conductive members and catalyst particles, the catalyst ink also contains a dispersion medium such as water, ethanol, or propanol. The catalyst ink may further contain particulate conductive members, a proton-conductive resin, etc.

[0154] Examples of application methods include spraying, screen printing, and coating methods using various coaters such as a blade coater, a knife coater, a gravure coater, etc. When a coater is used, it is easy to control the tilt direction of the first fibrous conductive members.

[0155] Since it is easy to obtain first fibrous conductive members that are inclined with respect to the XY direction, when forming a catalyst layer by applying catalyst ink, it is preferable to adjust the length of the first fibrous conductive members and the thickness of the catalyst layer so that L1 / T1 is 3 or less. The length of the first fibrous conductive members can be adjusted by appropriately selecting the length of the material used for the first fibrous conductive members. The thickness of the catalyst layer can be adjusted by changing the amount of catalyst ink applied, etc.

[0156] The inclination angle θ of the first fibrous conductive members can be adjusted by, for example, changing the composition, viscosity, application amount, application speed, drying speed, etc. of the catalyst ink.

[0157] (gas diffusion layer) The gas diffusion layer is composed of a porous layer whose main components are a conductive material and a polymer resin. The porous layer contains a mixture of a conductive material and a polymer resin. The porous layer (conductive material) does not include woven or nonwoven fabrics containing carbon fibers, such as carbon cloth or carbon paper, or sheet-like porous substrates, such as metal mesh or porous metal sheets, such as expanded metal. From the viewpoint of ensuring gas diffusibility and conductivity, the content of the conductive material in the gas diffusion layer (porous layer) is preferably 50% by mass or more and 90% by mass or less.

[0158] Examples of conductive materials include fibrous materials (second fibrous conductive members), particulate materials, and plate-like materials. Among these, the conductive material preferably includes second fibrous conductive members. The voids formed by the second fibrous conductive members in the gas diffusion layer communicate with the voids formed by the first fibrous conductive members in the catalyst layer, thereby efficiently discharging generated water from the catalyst layer to the gas diffusion layer. The second fibrous conductive members may be those exemplified as the first fibrous conductive members. The proportion of the second fibrous conductive members in the total conductive material is preferably 10% by mass or more and 80% by mass or less, more preferably 20% by mass or more and 75% by mass or less.

[0159] From the viewpoint of improving the discharge of generated water from the catalyst layer to the gas diffusion layer, the ratio of the length L2 of the second fibrous electrically conductive members to the length L1 of the first fibrous electrically conductive members, L2 / L1, is preferably 0.5 or more, more preferably 1.0 or more, and even more preferably more than 1.0. Furthermore, L2 / L1 is preferably 200 or less, more preferably 10 or less.

[0160] The length L2 of the second fibrous conductive members is the average fiber length, and is determined by randomly selecting 10 second fibrous conductive members from the gas diffusion layer and averaging the fiber lengths of these second fibrous conductive members. Note that the fiber length of the second fibrous conductive members refers to the length of a straight line connecting one end of the second fibrous conductive members to the other end.

[0161] The length L2 of the second fibrous conductive members is preferably 0.5 μm or more and 100 μm or less, more preferably 1.0 μm or more and 20 μm or less. In this case, a thin gas diffusion layer (e.g., a thickness T2 of 150 μm or less) can be easily formed, which is advantageous for miniaturizing fuel cells. Furthermore, the voids formed by the second fibrous conductive members in the gas diffusion layer are easily connected to the voids formed by the first fibrous conductive members in the catalyst layer, which allows for efficient discharge of generated water from the catalyst layer to the gas diffusion layer.

[0162] To ensure efficient discharge of produced water from the catalyst layer to the gas diffusion layer, the ratio of the diameter D2 of the second fibrous electrically conductive members to the diameter D1 of the first fibrous electrically conductive members (D2 / D1) is preferably 0.5 or more, more preferably 1.0 or more, and even more preferably greater than 1.0. Furthermore, D2 / D1 is preferably 30 or less, more preferably 20 or less.

[0163] The diameter D2 of the second fibrous conductive members is determined by randomly selecting 10 second fibrous conductive members from the gas diffusion layer and averaging their diameters. The diameter is the length perpendicular to the length of the second fibrous conductive members.

[0164] The diameter D2 of the second fibrous conductive members is preferably 200 nm or less, and more preferably 10 nm or more and 180 nm or less, in which case the volume ratio of the second fibrous conductive members in the gas diffusion layer can be reduced, ensuring sufficient gas paths and further improving gas diffusibility.

[0165] When viewed microscopically, particulate materials are composed of spherical particles or irregular particles. However, spherical particles do not usually exist as completely unoriented spheres, but rather have a long diameter and a short diameter. The maximum diameter (long diameter) L of a spherical particle or irregular particle is a and the maximum diameter (minor diameter) W that is perpendicular to the maximum diameter a That is, L a ≧W a The aspect ratio of the particulate material is L. a / W a is 1≦L a / Wa ≦5, and 1≦L a / W a It is more preferable that <2 is satisfied.

[0166] Examples of particulate materials include carbon black, spherical graphite, and activated carbon. Among these, carbon black is preferred because of its high conductivity and large pore volume. Examples of carbon black that can be used include acetylene black, ketjen black, and furnace black.

[0167] Plate-like materials are granular when viewed macroscopically, but are composed of plate-like particles when viewed microscopically. The minimum width (thickness) of a plate-like particle is T b When the thickness T is measured, the maximum diameter (longest diameter) of the plate-like particle as viewed in a direction parallel to the thickness T is L. b and the maximum diameter (minor diameter) W that is perpendicular to the maximum diameter b That is, L b ≧W b Meet T b is W b The aspect ratio of the plate material is L b / T b is 10 <L b / T b It is preferable that 20≦L b / T b It is more preferable that the following be satisfied.

[0168] Specific examples of the plate-like material include flake graphite, pulverized graphitized polyimide film, graphene, etc. Among them, pulverized graphitized polyimide film and graphene are easily oriented in the plane direction of the gas diffusion layer, and are advantageous for forming a thin gas diffusion layer.

[0169] The polymer resin functions as a binder that binds conductive materials together. From the viewpoint of suppressing water retention in the pores in the gas diffusion layer, it is preferable that 50% by mass or more, and even 90% by mass or more of the polymer resin is a water-repellent fluororesin. Examples of fluororesins include PTFE (polytetrafluoroethylene), FEP (tetrafluoroethylene-hexafluoropropylene copolymer), PVdF (polyvinylidene fluoride), ETFE (tetrafluoroethylene-ethylene copolymer), PCTFE (polychlorotrifluoroethylene), and PFA (polyfluoroethylene-perfluoroalkyl vinyl ether copolymer). Among these, from the viewpoints of heat resistance, water repellency, and chemical resistance, it is preferable that the fluororesin be PTFE.

[0170] The polymer resin is preferably 2 parts by mass or more and 70 parts by mass or less, and more preferably 10 parts by mass or more and 60 parts by mass or less, per 100 parts by mass of the conductive material contained in the gas diffusion layer.

[0171] The ratio of the thickness T2 of the gas diffusion layer to the thickness T1 of the catalyst layer: T2 / T1 is preferably 1.0 or more and 75 or less, and more preferably 1.5 or more and 50 or less. In this case, the supply of the reactant gas from the gas diffusion layer to the catalyst layer and the discharge of the generated water from the catalyst layer to the gas diffusion layer are efficiently carried out.

[0172] The thickness T2 of the gas diffusion layer is preferably 600 μm or less, more preferably 150 μm or less, and even more preferably 30 μm or more and 150 μm or less. If the average thickness of the gas diffusion layer designed as described above is too large, the gas diffusion path length in the thickness direction becomes long, and it tends to be difficult to improve power generation performance. If the thickness of the gas diffusion layer is 30 μm or more, it is easy to ensure a balanced gas diffusion path length in the thickness direction and in the plane direction.

[0173] When the first main surface of the gas diffusion layer and the opposite second main surface are visually flat without irregularities due to cutting or press processing, the thickness T2 of the gas diffusion layer can be determined by measuring the thickness of the gas diffusion layer at 10 arbitrary locations and averaging these thicknesses. On the other hand, when the gas diffusion layer has an irregular pattern, the maximum and minimum thicknesses of the gas diffusion layer can be determined, multiplied by their area ratios, and then added. The maximum thickness of the gas diffusion layer can be determined as the average thickness of the thickest portions of 10 arbitrary locations of the protrusions, and the minimum thickness of the gas diffusion layer can be determined as the average thickness of the thinnest portions of 10 arbitrary locations of the recesses. When the thickness T2 of the gas diffusion layer is 150 μm or less, or even 100 μm or less, it is preferable that the two main surfaces of the gas diffusion layer are visually flat without the aforementioned irregularities.

[0174] From the viewpoint of gas diffusion properties and drainage properties, the porosity P2 of the gas diffusion layer is preferably 60% or more and 90% or less, and more preferably 65% ​​or more and 88% or less.

[0175] From the viewpoint of efficient supply of reaction gas from the gas diffusion layer to the catalyst layer and efficient discharge of generated water from the catalyst layer to the gas diffusion layer, the ratio of the porosity P2 of the gas diffusion layer to the porosity P1 of the catalyst layer: P2 / P1 is, for example, 0.7 or more, and preferably greater than 1. When P2 / P1 exceeds 1, drainage can be further improved. Furthermore, P2 / P1 is, for example, 3.0 or less.

[0176] The porosity P2 of the gas diffusion layer is determined as follows.

[0177] A scanning electron microscope (SEM) is used to take an image of the cross section of the gas diffusion layer. The obtained image is then subjected to image processing (binarization processing) so that the voids and non-voids can be distinguished. A region of a predetermined area A2 is arbitrarily selected from the processed image, and the area A of the voids present in that region is calculated. p2 Calculate the area of ​​the void A relative to the area A2 of the region. p2 The ratio (%) of the above is calculated and set as the porosity P2. A plurality of porosities may be calculated for a plurality of regions, and these may be averaged.

[0178] (Formation of gas diffusion layer) The process for forming the porous layer used in the gas diffusion layer includes, for example, a first step of preparing a mixture containing a conductive material, a polymer resin, a surfactant, and a dispersion medium, a second step of molding the mixture to obtain a sheet, a third step of firing the molded sheet, and a fourth step of rolling the fired sheet.

[0179] In the first step, a kneader or a mixer may be used as the mixing device. Preferably, the conductive material, surfactant, and dispersion medium are introduced into the mixing device to uniformly disperse the conductive material in the dispersion medium, and then a polymer resin is added to further disperse the conductive material. It is preferable to apply an appropriate shear force to the polymer resin to fibrillate it. Examples of the dispersion medium include water, alcohol, and glycols. Examples of the surfactant include polyoxyethylene alkyl ether, alkylamine oxide, and the like.

[0180] In the second step, for example, the mixture is extrusion-molded. The obtained molded sheet may be further rolled. A roll press machine can be used for rolling. The conditions for the roll press are not particularly limited, but rolling at a linear pressure of 0.001 ton / cm to 4 ton / cm makes it easier to obtain a gas diffusion layer with high strength.

[0181] In the third step, the sheet is baked to remove the surfactant and dispersion medium. The baking temperature may be any temperature at which the polymer resin does not deteriorate and at which the surfactant and dispersion medium decompose or volatilize. When PTFE is used as the polymer resin, the baking temperature is preferably 310 to 340°C. The baking atmosphere may be an inert atmosphere, such as a nitrogen or argon atmosphere, or a reduced pressure atmosphere. It is sufficient that most of the surfactant and dispersion medium are removed from the sheet, but they do not necessarily have to be completely removed.

[0182] In the fourth step, the fired sheet is rolled to adjust its thickness. Alternatively, grooves serving as gas channels may be formed on at least one of the two main surfaces of the fired sheet by providing ribs with a predetermined gas channel pattern on the die used for rolling. The method for forming the gas channels is not limited to the press working described above; the gas channels may also be formed by cutting the main surface of the rolled sheet.

[0183] An example of the structure of a fuel cell according to this embodiment will be described below with reference to FIG. 6. FIG. 6 is a cross-sectional view that schematically shows the structure of a unit cell that is arranged in a fuel cell according to this embodiment of the present invention. Typically, a plurality of unit cells are stacked and arranged in the fuel cell as a cell stack. For convenience, FIG. 6 shows one unit cell.

[0184] Each unit cell of the fuel cell 200 includes a membrane electrode assembly 100 having an electrolyte membrane 110, a first catalyst layer 120A and a second catalyst layer 120B arranged to sandwich the electrolyte membrane 110, and a first gas diffusion layer 130A and a second gas diffusion layer 130B arranged to sandwich the electrolyte membrane 110, with the first catalyst layer 120A and the second catalyst layer 120B interposed therebetween. The unit cell of the fuel cell 200 also includes a first separator 240A and a second separator 240B sandwiching the membrane electrode assembly 100. One of the first catalyst layer 120A and the second catalyst layer 120B functions as an anode, and the other functions as a cathode. Because the electrolyte membrane 110 is slightly larger than the first catalyst layer 120A and the second catalyst layer 120B, the peripheral edge of the electrolyte membrane 110 protrudes from the first catalyst layer 120A and the second catalyst layer 120B. The peripheral edge of the electrolyte membrane 110 is sandwiched between a pair of sealing members 250A and 250B.

[0185] At least one of the first catalyst layer 120A and the second catalyst layer 120B is the catalyst layer 120 shown in FIG. 7. FIG. 7 is a diagram schematically illustrating the interior of the catalyst layer, viewed from the planar direction. For convenience, the electrolyte membrane 110 is also shown to illustrate the inclination of the fibrous conductive members. As shown in FIG. 7, the catalyst layer 120 includes first fibrous conductive members 121A and catalyst particles 122. The first fibrous conductive members 121A are inclined with respect to the planar direction (XY direction) of the electrolyte membrane 110. If the first catalyst layer 120A or the second catalyst layer 120B is not the above-described catalyst layer 120, a known material and a known configuration can be used as the catalyst layer.

[0186] At least one of the first gas diffusion layer 130A and the second gas diffusion layer 130B is formed of the porous layer described above. If the first gas diffusion layer 130A or the second gas diffusion layer 130B is not formed of a porous layer, the gas diffusion layer may be formed of a known material and have a known structure.

[0187] A polymer electrolyte membrane is preferably used as the electrolyte membrane 110. Materials for the polymer electrolyte membrane include the polymer electrolytes exemplified as the proton conductive resin. The thickness of the electrolyte membrane 110 is, for example, 5 to 30 μm.

[0188] The first separator 240A and the second separator 240B may be made of any material, as long as they are airtight, electronically conductive, and electrochemically stable. Carbon materials, metal materials, and the like are preferred. Metal materials may be coated with carbon. For example, the first separator 240A and the second separator 240B can be obtained by punching a metal plate into a predetermined shape and then subjecting it to a surface treatment.

[0189] In this embodiment, a gas flow channel 260A is formed on the surface of the first separator 240A that comes into contact with the first gas diffusion layer 130A. Meanwhile, a gas flow channel 260B is formed on the surface of the second separator 240B that comes into contact with the second gas diffusion layer 130B. The shape of the gas flow channel is not particularly limited, and may be a parallel type, a serpentine type, a straight type, or the like.

[0190] Seal members 250A, 250B are made of an elastic material and prevent leakage of fuel and / or oxidant from gas flow paths 260A, 260B. Seal members 250A, 250B have, for example, a frame-like shape that surrounds the peripheral edges of first catalyst layer 120A and second catalyst layer 120B in a loop shape. Seal members 250A, 250B can each be made of a known material and have a known configuration. [Industrial Applicability]

[0191] The fuel cell according to the present disclosure can be suitably used as a power source for a stationary household cogeneration system or a vehicle power source. The present disclosure is suitable for application to a polymer electrolyte fuel cell, but is not limited thereto, and can be applied to fuel cells in general. [Explanation of symbols]

[0192] 100 Membrane electrode assembly 110 Electrolyte membrane 120 Catalyst layer 120A 1st catalyst layer 120B 2nd catalyst layer 120X 1st main surface 120Y Second principal surface 121 Fibrous conductive material 121A first fibrous conductive member 122 Catalytic particles 122A 1st particle 122B Core 122C Shell 130A First gas diffusion layer 130B Second gas diffusion layer 200 Fuel Cell 240A First Separator 240B Second separator 250A, 250B sealing material 260A, 260B gas flow path

Claims

1. A method for manufacturing a catalyst layer for a fuel cell, the method comprising: a length L which is an average fiber length of the fibrous conductive member and a thickness T which is an average thickness of the fuel cell catalyst layer satisfy the relational formula: 0.25≦L / T≦1.0, The length L is 0.5 μm or more and 10 μm or less, The thickness T is 2 μm or more and 20 μm or less, the fibrous conductive member is inclined with respect to a surface direction of the fuel cell catalyst layer, preparing an ink containing the fibrous conductive members and catalyst particles; a step of applying the ink to a surface of an electrolyte membrane and drying the ink to form the catalyst layer, or a step of applying the ink to a transfer substrate sheet and drying the ink to form a catalyst layer, and then transferring the catalyst layer to the electrolyte membrane.

2. The method for producing a catalyst layer for a fuel cell according to claim 1 , wherein an inclination angle θ of the fibrous conductive member with respect to a surface direction of the catalyst layer for a fuel cell is 80° or less.

3. The length L of the fibrous conductive member and the diameter D of the fibrous conductive member are related by the following formula: D / L<1 The method for producing a catalyst layer for a fuel cell according to claim 1 or 2, which satisfies the above.

4. The method for producing a fuel cell catalyst layer according to any one of claims 1 to 3, wherein the fibrous conductive members have a diameter D of 200 nm or less.

5. The method for producing a catalyst layer for a fuel cell according to any one of claims 1 to 4, further comprising the step of: adding 40 parts by mass or less of particulate conductive material per 100 parts by mass of the total of the fibrous conductive material and the particulate conductive material.

6. The method for producing a fuel cell catalyst layer according to any one of claims 1 to 5, wherein the fibrous conductive member has a BET specific surface area of ​​50 m2 / g or more.

7. The fuel cell comprises a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane, A method for producing a fuel cell, wherein at least one of the pair of electrodes is formed by the method for producing a catalyst layer according to any one of claims 1 to 6.

8. A method for manufacturing a catalyst layer for a fuel cell, the method comprising: a length L which is an average fiber length of the fibrous conductive member and a thickness T which is an average thickness of the fuel cell catalyst layer satisfy the relational formula: 0.25≦L / T≦1.0, The length L is 0.5 μm or more and 10 μm or less, The thickness T is 2 μm or more and 20 μm or less, the fibrous conductive member is inclined with respect to a surface direction of the fuel cell catalyst layer, The catalyst particles include a first particle having a core portion and a shell portion, the shell portion covers the core portion and contains a component different from that of the core portion, preparing an ink containing the fibrous conductive members and catalyst particles; a step of applying the ink to a surface of an electrolyte membrane and drying the ink to form the catalyst layer, or a step of applying the ink to a transfer substrate sheet and drying the ink to form a catalyst layer, and then transferring the catalyst layer to the electrolyte membrane.

9. the core portion contains at least one of palladium and a palladium alloy, The method for producing a fuel cell catalyst layer according to claim 8 , wherein the shell portion contains at least one of platinum and a platinum alloy.

10. The method for producing a fuel cell catalyst layer according to claim 8 , wherein the first particles have an average particle size of 2 nm or more and 10 nm or less.

11. The method for producing a fuel cell catalyst layer according to any one of claims 8 to 10, wherein the catalyst particles further include second particles containing the same components as the core portion.

12. The method for producing a fuel cell catalyst layer according to any one of claims 8 to 11, wherein the catalyst particles further include a third particle containing the same component as the shell portion.

13. The fuel cell comprises a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane, A method for producing a fuel cell, wherein at least one of the pair of electrodes is formed by the method for producing a catalyst layer according to any one of claims 8 to 12.

14. A method for producing a membrane electrode assembly including an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane, the method comprising the steps of: each of the pair of electrodes includes, in order from the electrolyte membrane side, a catalyst layer and a gas diffusion layer; the catalytic layer of at least one of the pair of electrodes includes a first fibrous conductive member and catalytic particles; The length L which is the average fiber length of the first fibrous conductive member 1 and the average thickness T of the catalyst layer. 1 and the relation: 0.25≦L 1 / T 1 ≦1.0, The length L 1 is 0.5 μm or more and 10 μm or less, The thickness T 1 is 2 μm or more and 20 μm or less, the first fibrous conductive members are inclined with respect to a surface direction of the catalyst layer, the gas diffusion layer of at least one of the pair of electrodes is formed of a porous layer containing a conductive material and a polymer resin, preparing an ink containing the first fibrous conductive members and catalyst particles; a step of applying the ink to a surface of an electrolyte membrane and drying the ink to form the catalyst layer, or a step of applying the ink to a transfer substrate sheet and drying the ink to form a catalyst layer, and then transferring the catalyst layer to the electrolyte membrane.

15. The method for producing a membrane electrode assembly according to claim 14, wherein the gas diffusion layer has a thickness at least twice as large as a thickness of the catalyst layer.

16. The method for producing a membrane electrode assembly according to claim 14 or 15, wherein the gas diffusion layer has a thickness of 600 µm or less.

17. The method for producing a membrane electrode assembly according to any one of claims 14 to 16, wherein the conductive material includes a second fibrous conductive member.

18. 20. The method of claim 17, wherein a length of the second fibrous conductive members is greater than a length of the first fibrous conductive members.

19. 19. The method for manufacturing a membrane electrode assembly according to claim 17 or 18, wherein a diameter of the second fibrous conductive members is larger than a diameter of the first fibrous conductive members.

20. The porosity P of the catalyst layer 1 is 30% or more and 70% or less, The porosity P of the gas diffusion layer 2 The method for producing a membrane / electrode assembly according to any one of claims 14 to 19, wherein the ratio of the solubility of the polymer to the total surface area of ​​the membrane / electrode assembly is 60% or more and 90% or less.

21. The porosity P of the catalyst layer 1 and the porosity P of the gas diffusion layer. 2 And, P 1 <P 2 The method for producing a membrane electrode assembly according to claim 20, wherein the above-mentioned relationship is satisfied.

22. A membrane electrode assembly and a pair of separators sandwiching the membrane electrode assembly, A method for producing a fuel cell, wherein the membrane electrode assembly is formed by the method according to any one of claims 15 to 21.

Citation Information

Patent Citations

  • Fuel cell, and method for fabrication same

    JP2007257886A

  • Cell for fuel cell, its manufacturing method, and polymer electrolyte fuel cell

    JP2007273269A

  • Method for producing carbon-carried core-shell type catalyst fine particle, method for producing catalyst ink using the core-shell type catalyst fine particle obtained by the production method, and catalyst layer containing the catalyst ink obtained by the production method

    JP2011218278A

  • Membrane electrode assembly and fuel cell, and manufacturing method therefor

    JP2014035797A

  • Fuel cell membrane-electrode assembly

    WO2013065396A1